An investigation into the physico-chemical and neuroprotective properties of melatonin and 6-hydroxymelatonin - Maharaj, Deepa Sukhdev (Rhodes University, Faculty of Pharmacy, Pharmacy, 2003)
Until the beginning of this decade the antioxidant, melatonin, had been considered as little more than a tranquilizing hormone, responsible for regulating certain circadian and circannual rhythms. However, it is the discovery of melatonin as a free radical scavenger that has generated the most interest in recent years. The reduction of melatonin with age has been associated with neurodegenerative diseases such as Alzheimer's disease (AD)and therefore, melatonin has been implicated to have an important clinical role in neuroprotection. Thus, for several years melatonin has attracted increasing attention from the general press with many advertisements touting this indoleamine to act as an aphrodisiac, rejuvenator, protector against diseases and a general wonder drug. However, melatonin formulations appear with no labelling for the correct storage conditions, dosage and side effects, as well as no control for purity and self-medicating with an unregulated product. In addition, there is much controversy surrounding the antioxidative properties of the indolemaine, 6-hydroxymelatonin (6-OHM). Therefore, the first part of this study aims to elucidate the physico-chemical and various stability characteristics of the pineal antioxidant, melatonin, while the second part is devoted to investigating the neuroprotective properties of the primary hepatic metabolite of melatonin, 6-OHM. The physical properties of melatonin were determined using various chemical techniques. This information served to both characterize and confirm the identity of melatonin raw material used in this study. In addition, this information serves to be essential as the physical properties of melatonin have not been reported in detail in literature, to date. Thereafter, using a validated high performance liquid chromatography (HPLC) method, the various physico-chemical and stability characteristics of melatonin were determined. Melatonin was shown to be extremely lipophilic, while the hygroscopic study indicates that melatonin raw material is extremely hygroscopic at temperatures above 40Â°C, whereas melatonin tablets are hygroscopic when left out of the original container. This study highlights the need for consumers to be aware of the proper storage of melatonin tablets to improve the stability and ensure long term integrity of the compound. Since, melatonin is most often administered orally, thus exposing it to a large variations in pH, within the gastrointestinal tract, it was decided to investigate the stability of melatonin over a range of pH's and temperatures. The findings imply that melatonin is relatively stable at body temperature when ingested orally and that orally administered slow release preparations of melatonin should be relatively stable and therefore exhibit favourable bioavailability. However melatonin was shown to be unstable in solution. This provides important information and a challenge to the formulators of this drug substance in a liquid dosage form. An assessment of the photostability of melatonin dosage forms using International Committee on Harmonization (ICH) conditions revealed melatonin to be light sensitive and thus indicates a need for careful consideration of the packaging of these drug products. In addition a detailed assessment of the photochemistry and photoproducts formed during the UV photodegradation of melatonin is reported. Melatonin is shown to rapidly degrade in the presence of UV light, with the presence of oxygen accelerating the photodegradation. N1-acetyl-N2-formyl-5-methoxykynurenamine(AFMK) and 6-OHM were identified as the major photoproducts formed and these agents have been shown previously to retain antioxidant activity. One of the concerns of using melatonin in sunscreens is its photostability. However, it is reported in this study that the degraded solution of melatonin still possesses equipotent free radical scavenging ability as melatonin, despite the absence of melatonin in solution. In addition, melatonin is shown to reduce UV-induced oxidative stress in rat skin homogenate. Thus, these results make melatonin a likely candidate for inclusion in sunscreen preparations. Neuronal damage due to oxidative stress has been implicated in several neurodegenerative disorders. 6-OHM is not only formed as the major hepatic metabolite of melatonin, but also when melatonin reacts with toxic radicals as well as UV light. Thus the second part of the study aims to elucidate and further characterize the mechanism behind 6-OHM's neuroprotection. The results show 6-OHM to be a more potent singlet oxygen and superoxide anion scavenger than melatonin. In addition, the results show 6-OHM to offer protection against, oxidative stress and lipid peroxidation induced by several neurotoxins in the rat brain and hippocampus. The hippocampus is an important region of the brain responsible for the formation of memory and any agent that induces stress in this area has detrimental effects and could lead to various types of dementia. Such agents include quinolinic acid (QA) and iron (II). Histological studies undertaken reveal that 6-OHM is able to protect hippocampal neurons against QA and iron (II) induced necrotic cell death. Immunohistochemical investigations showed that QA moderately induces apoptotic cell death in the hippocampus which is inhibited by both melatonin and 6-OHM. The study sought to elucidate possible mechanisms by which 6-OHM exerts its neuroprotective capabilities and the results show 6-OHM to inhibit the action of cyanide on the mitochondrial electron transport chain (ETC), one of the most common sources of free radicals. In addition, 6-OHM treatment alone, increased ETC activity above basal control levels and the results show 6-OHM to increase complex I activity in the mitochondrial ETC. Electrochemical, ultraviolet/visible spectroscopy (UV/Vis) and HPLC assessment show that an interaction exists between 6-OHM and iron (III) and 6-OHM is able to reduce iron (III) to a more biologically usable form viz. iron (II) which can be incorporated into important biomolecules such as heme. One dire consequence of this interaction is the ready provision of iron (II) to drive the Fenton reaction. However the biological and histological assessments show 6-OHM to prevent iron (II)-induced lipid peroxidation and necrotic cell death and thus, provide evidence of its antioxidant properties. The results also show 6-OHM to promote Hsp70 induction in the hippocampus. Heat shock proteins, especially Hsp 70 plays a role in cytoprotection by capturing denatured proteins and facilitating the refolding of these proteins once the stress has been relieved. 6-OHM treatment alone and together with QA was shown to increase the level of expression of Hsp70, both inducible and cognate forms of the protein. This suggests that 6-OHM helps to protect against cellular protein damage induced by any form of stress the cell may encounter. Melatonin treatment alone and in combination with QA was shown to prevent increases in the level of Hsp70 in the hippocampus, indicating that melatonin was able to reduce oxidative stress induced by QA such that Hsp70 expression was not required. The discovery of neuroprotective agents, such as melatonin and 6-OHM, is becoming important considering the rapid rise in the elderly population and the proportionate increase in neurological disorders. The findings of this study indicate the need for important information regarding the correct storage conditions and stability characteristics of melatonin dosage forms. In addition, the results indicate that 6-OHM has a definite role to play as an antioxidant. Thus further research may favour the use of these agents in the treatment of several neurodegenerative disorders.
Keywords: Melatonin; Nervous system -- Degeneration -- Treatment